2001
DOI: 10.1007/s004640000270
|View full text |Cite
|
Sign up to set email alerts
|

Shorter postoperative atony after laparoscopic-assisted colonic resection?

Abstract: These results support the hypothesis that laparoscopic-assisted resection of the colon leads to a shortened postoperative atony in comparison to open surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 21 publications
0
7
0
1
Order By: Relevance
“…Also, whenever the procedure is converted after part of the dissection is performed laparoscopically, there is no need for a large amount of manipulation and mobilization of the abdominal contents for exposure. It has been shown in animal studies that the laparoscopic-assisted resections lead to a shortened postoperative ileus compared with open surgery, which is evidenced by a significantly earlier restoration of intestinal motility indicated by the electric activity front of the migrating motility complex 20 and lower levels of gut cytokines. 21 Consequently, less pain and faster bowel recovery may account for faster discharge of the patient from the hospital.…”
Section: Discussionmentioning
confidence: 99%
“…Also, whenever the procedure is converted after part of the dissection is performed laparoscopically, there is no need for a large amount of manipulation and mobilization of the abdominal contents for exposure. It has been shown in animal studies that the laparoscopic-assisted resections lead to a shortened postoperative ileus compared with open surgery, which is evidenced by a significantly earlier restoration of intestinal motility indicated by the electric activity front of the migrating motility complex 20 and lower levels of gut cytokines. 21 Consequently, less pain and faster bowel recovery may account for faster discharge of the patient from the hospital.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies also demonstrate earlier recovery of bowel motility with laparoscopic compared with open procedures. [14][15][16][17][18][19] Time to first defecation and mouth to anus transit times have been previously shown to be shorter in dogs undergoing laparoscopic surgery compared with open partial pancreatectomy. 20…”
Section: Discussionmentioning
confidence: 99%
“…Experimental and clinical studies have shown that laparoscopic surgery, in general, is associated with a lower incidence of postoperative ileus [6,7]. However, the effect of laparoscopic cholecystectomy on colonic motility has thus far, to the best of the authors' knowledge, only been studied sparingly.…”
Section: Background and Purposementioning
confidence: 98%